The Effect Of Health Education On Pregnant Women's Attitudes And Knowledge Towards Congenital Hypothyroid Screening (CHC) At The Clinik Dermawati , Tembung Deli Serdang - Suyanti Suwardi; Dian Zuiatna (Journal of Innovative and Creativity, 2026)
Background; Congenital hypothyroidism is an endocrine disorder in newborns that can cause growth and developmental delays if not detected and treated early. This study aims to determine the effect of health education on pregnant women's knowledge and attitudes regarding Congenital Hypothyroidism Screening (CHS) at Dermawati Clinic, Tembung Deli Serdang, in 2025. Methods;This study used a quasi-experimental design with a pretest-posttest with a control group. The sample size was 62 pregnant women: 31 with the education treatment and 31 without treatment. The research instrument was a knowledge and attitude questionnaire, and data analysis used a t-test.The results showed that regarding knowledge, before the intervention, the majority of respondents in the control group had poor knowledge (90.3%), and after the intervention, all respondents in the experimental group had good knowledge (100%). Regarding attitude, before the intervention, all respondents in the control group had negative attitudes (100%), while after the intervention, all respondents in the experimental group had positive attitudes (100%). The statistical test results showed a p-value of 0.000 (p < 0.05) for both variables, indicating a significant effect of health education on pregnant women's knowledge and attitudes regarding SHK. Results;The conclusion of this study is that health education delivered in a structured, relevant, and interactive manner can increase knowledge and shape positive attitudes among pregnant women toward SHK implementation. It is recommended that health education be included as a routine part of antenatal care services to support early detection of congenital hypothyroidism in newborns.